Carbon Nano-onions: Potassium Intercalation and Reductive Covalent Functionalization - Perez-Ojeda Rodriguez, Maria Eugenia; Castro, Edison; Kröckel, Claudia; Lucherelli, Matteo Andrea; Ludacka, Ursula; Kotakoski, Jani; Werbach, Katharina; Peterlik, Herwig; Melle-Franco, Manuel; Chacón-Torres, Julio C.; Hauke, Frank; Echegoyen, Luis; et al. (Journal of the American Chemical Society, 2021)
Herein we report the synthesis of covalently functionalized carbon nano-onions (CNOs) via a reductive approach using unprecedented alkali-metal CNO intercalation compounds. For the first time, an in situ Raman study of the controlled intercalation process with potassium has been carried out revealing a Fano resonance in highly doped CNOs. The intercalation was further confirmed by electron energy loss spectroscopy and X-ray diffraction. Moreover, the experimental results have been rationalized with DFT calculations. Covalently functionalized CNO derivatives were synthesized by using phenyl iodide and n-hexyl iodide as electrophiles in model nucleophilic substitution reactions. The functionalized CNOs were exhaustively characterized by statistical Raman spectroscopy, thermogravimetric analysis coupled with gas chromatography and mass spectrometry, dynamic light scattering, UV–vis, and ATR-FTIR spectroscopies. This work provides important insights into the understanding of the basic principles of reductive CNOs functionalization and will pave the way for the use of CNOs in a wide range of potential applications, such as energy storage, photovoltaics, or molecular electronic